2021
DOI: 10.2106/jbjs.cc.21.00240
|View full text |Cite
|
Sign up to set email alerts
|

Polymetatarsia of the Foot without Polydactyly

Abstract: Case: We report a rare case of polymetatarsia without polydactyly. Our patient presented with pain and difficulty with shoewear. Radiographs showed an accessory metatarsal arising from the lateral aspect of the fourth metatarsal proximal metaphysis, fusing distally with the medial aspect of the fifth metatarsal head to form a single metatarsophalangeal joint. He was treated with a chevron osteotomy of the conjoined complex and an Akins osteotomy of the fifth proximal phalanx. Our patient recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Oragui et al 21 described the case of a 17-year-old girl with an extrametatarsal head with a duplicated fusion of the proximal phalanx, and Han et al 18 reported a case of polydactyly of the fourth metatarsal treated by bone transfer of the extrametatarsal bone and subsequent fixation with an internal plate. But polydactyly is not always visible, as reported in a case of polymetatarsia or metatarsal duplication associated with nonvisible polydactyly 25 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Oragui et al 21 described the case of a 17-year-old girl with an extrametatarsal head with a duplicated fusion of the proximal phalanx, and Han et al 18 reported a case of polydactyly of the fourth metatarsal treated by bone transfer of the extrametatarsal bone and subsequent fixation with an internal plate. But polydactyly is not always visible, as reported in a case of polymetatarsia or metatarsal duplication associated with nonvisible polydactyly 25 …”
Section: Discussionmentioning
confidence: 93%
“…There exists a paucity of guidelines on the surgical management of polymetatarsia. 25 The presentation of postaxial polydactyly is very varied and may require different treatment modalities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations